Determinasi Kompetensi Penyuluh Keluarga Berencana di Provinsi Aceh (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
This study aims to analyze the determinants of the family planning instructor's competence in Aceh Province. The research method used primary data on three different residential characteristics (Aceh Utara, Aceh Selatan, and Aceh Tengah). Collecting data by means of direct interviews with family planning counselors as many as 97 people using a questionnaire. The instruments are prepared based on the standard indicators of Family Planning Extension competency (Perka BKKBN No.2 of 2017). Each question is measured using a linkert scale and analyzed using the Relative Important Index (RII) formula. The descriptive results state that the competency standards of family planning instructors in Aceh Province are in the competent category in technical, managerial and socio-cultural aspects. The most competent technical aspects are collecting data, planning, drafting and counseling the Bangga Kencana program. The managerial aspect is the most competent in seeking information and establishing cooperation in implementing the Bangga Kencana program in the field. Meanwhile, the socio-cultural aspect is the most competent in having a national perspective.